Cobalt Single‐Atom Electrocatalysts Enhanced by Hydrogen‐Bonded Organic Frameworks for Long‐Lasting Zinc‐Iodine Batteries - Guo, Chaofei; Cao, Yingnan; Gao, Yun; Zhi, Chuanwei; Wang, Yu‐Xuan; Luo, Yuhan; Yang, Xue‐Juan; Luo, Xiping (Advanced functional materials, 2024)
Herein, a hydrogen‐bonded cobalt porphyrin framework is presented that can efficiently host iodine and serve as an electrocatalyst for aqueous zinc‐iodine (Zn‐I2) organic batteries. The Fourier Transform infrared spectroscopy (FT‐IR), X‐ray Photoelectron Spectroscopy (XPS), and Density functional theory (DFT) results demonstrate that hydrogen‐bonded organic frameworks (HOFs) possess excellent adsorption properties for iodine species. In situ Raman spectroscopy illustrates that the redox mechanism of Zn‐I2 battery depends on the redox reaction of I/I−, with I3−/I5− serving as intermediary products. The in situ Ultraviolet‐visible (UV–vis) spectroscopy further reveals that HOFs restrict polyiodide solubilization. The aqueous Zn‐I2 organic batteries with I2@PFC‐72‐Co cathodes exhibit excellent rate capability, achieving 134.9 mAh g−1 at 20 C. Additionally, these batteries demonstrate long‐term cycle stability, enduring > 5000 cycles at 20 C. The impressive electrochemical performance of I2@PFC‐72‐Co can be attributed to the cooperative Co single‐atom (CoSA) electrocatalyst in the HOF‐Co structure. Moreover, the benzene ring structure and the carboxyl functional group of HOFs possess a strong ability to adsorb iodine and iodide. Owing to these synergistic effects, the aqueous Zn‐I2 batteries with the I2@PFC‐72‐Co cathode exhibit excellent electrochemical performance. A hydrogen‐bonded cobaltporphyrin framework (PFC‐72‐Co) is obtained for zinc‐iodine organic batteries. The in situ ultraviolet‐visible, in situ Raman, and density functional theory reveal that PFC‐72‐Co can effectively restrict the shuttle effect of polyiodide. As a consequence, the superior electrochemical properties can be achieved through the cobalt single‐atom electrocatalysts and physicochemical confinement effect of hydrogen‐bonded organic framework based electrodes.